Cultural policy in Ust-Tsilma (Russia) between neoliberalism and sustainability - Tonkova, Elena; Nosova, Tatyana (Lapin yliopisto, 2017)
The article analyses the cultural policies and practices in the municipal district of Ust-Tsilma (Komi Republic, Russia) from neoliberalism and sustainability perspectives. Ust-Tsilma was chosen as a case study for the broader NEO-BEAR research project1, which has aimed to establish how neoliberal and sustainability discourses change life in small municipalities in the Barents region. This study shows that the cultural sphere in the municipality of Ust-Tsilma is rapidly moving towards the neoliberal principles of organization of life, marked by economic and managerial efficiency, cultural consumerism, state–private financial partnership, competitive distribution of finances, and contract-based relations. Furthermore, the study shows that, in the context of declining population due to globalization and urbanization, a sustainability approach to culture (giving high priority to socialcultural capital, cultural heritage, and cultural landscape as well as to cultural access and participation) is extremely relevant for the future existence of the Ust-Tsilma municipality (and for the rural areas in general), because it brings a necessary adaptive potential for the survival of rural settlements and for the development of their communities.